2023
DOI: 10.3390/admsci13050135
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Effect of Nomination Committee’s Effectiveness on Board of Directors’ Characteristics and Firm Performance

Mujeeb Saif Mohsen Al-Absy,
Nada Hameed AlMahari

Abstract: This study aimed to examine the interaction effect of the nomination committee’s effectiveness on the board of directors’ characteristics and firm performance (measured by return on assets and earnings per share). The nomination committee was scored for committee separation, size, independence, meeting frequency, and the number of female directors. The study selected all listed firms on the Bahrain Bourse for two years, 2020 and 2021, using ordinary least-squares regression to examine the relationship. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…(2016) measure the quality of the remuneration committee with a composite score obtained from five characteristics of the remuneration committee, namely committee independence, committee size, independence of the committee chairman, committee expertise and committee meetings. Meanwhile, Al-Absy and AlMahari (2023) measured the effectiveness of the nomination committee using the nomination committee score (NCScore), which is the sum of five components (NC size, independence, meeting frequency, female directors and separation of the committee). All committee effectiveness measurements above have values ranging from 0 to 5, with 0 indicating the lowest effectiveness and 5 indicating the highest effectiveness.…”
Section: Measurement and Results Review Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…(2016) measure the quality of the remuneration committee with a composite score obtained from five characteristics of the remuneration committee, namely committee independence, committee size, independence of the committee chairman, committee expertise and committee meetings. Meanwhile, Al-Absy and AlMahari (2023) measured the effectiveness of the nomination committee using the nomination committee score (NCScore), which is the sum of five components (NC size, independence, meeting frequency, female directors and separation of the committee). All committee effectiveness measurements above have values ranging from 0 to 5, with 0 indicating the lowest effectiveness and 5 indicating the highest effectiveness.…”
Section: Measurement and Results Review Of Researchmentioning
confidence: 99%
“…, 2019). Al-Absy and AlMahari (2023) examine the moderating effect of nomination committee effectiveness. They found that the effectiveness of the nomination committee significantly positively moderated the relationship between the frequency of board meetings and the number of female directors and company performance.…”
Section: Measurement and Results Review Of Researchmentioning
confidence: 99%
See 1 more Smart Citation